ANALISIS PERTIMBANGAN MAHKAMAH AGUNG DALAM MENGABULKAN KASASI TERDAKWA (STUDI PUTUSAN NOMOR 2959/K/PID.SUS/2022) - Yaying Prabaswara; Bambang Santoso (Sebelas Maret University, 2023)
This study analyzesthe criminal procedural law related to the consideration of the Supreme Court which granted Cassation guilty in the Narcotics case in accordance with Article 253 paragraph (1) of the Criminal Procedure Code and the consideration of the Supreme Court whichannulled theJudex Factie decision and tried himself according to Article 256 jo 255 of the Criminal Procedure Code. The Supreme Court set an acquittal in this case because there were legal clues and facts that showed the Defendant was innocent. The research method used is normative legal research which is both perscriptive and applied with case studies. The way to collect legal materials is by studying the literature and legal materials used, namely primary and secondary legal materials. Based on the results of research and discussion to answer the problem, it can be concluded that the reasons for cassation submitted by the Defendant were in accordancewith Article 253 paragraph (1) letter a of the Criminal Procedure Code because in the reasons for cassation, theJudex Factiedecision had misapplied the law, ignoring facts and instructions indicating that the Defendant not guilty. The Supreme Court's considerations in granting the Defendant's cassation were in accordance with Article 256 jo 255 of the Criminal Procedure Code granted the cassation and annulled the Judex Factiedecision and the trial itself declared the convict not legally and convincingly proven guilty of committing a crime of Narcotics. The Supreme Court has restored the Defendant's rights in terms of ability, position and dignity.Keywords: defendant's cassation; Narcotics; Consideration of the Supreme Court;